2019
DOI: 10.1155/2019/3403206
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cav-1 in HIV-1 Tat-Induced Dysfunction of Tight Junctions and Aβ-Transferring Proteins

Abstract: Objective. To evaluate the role of caveolin-1 (Cav-1) in HIV-1 Tat-induced dysfunction of tight junction and amyloid β-peptide- (Aβ-) transferring proteins. Methods. A Cav-1 shRNA interference target sequence was cloned into the lentiviral vector pHBLV-U6-Scramble-ZsGreen-Puro and verified by double enzyme digestion and DNA sequencing. Human cerebral microvascular endothelium (HBEC-5i) cells were transduced with viral particles made in 293T cells by transfection with lentiviral packaging plasmids. HBEC-5i cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…Other studies, however, have suggested that cav‐1 may serve as an effective target for protecting against HIV‐1‐related disruption of the BBB 51 . Silencing the cav‐1 gene has also been described as having a key role in protecting against HIV‐1 by defending against HIV‐1 Tat‐induced downregulation of ocln 52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies, however, have suggested that cav‐1 may serve as an effective target for protecting against HIV‐1‐related disruption of the BBB 51 . Silencing the cav‐1 gene has also been described as having a key role in protecting against HIV‐1 by defending against HIV‐1 Tat‐induced downregulation of ocln 52 …”
Section: Discussionmentioning
confidence: 99%
“…51 Silencing the cav-1 gene has also been described as having a key role in protecting against HIV-1 by defending against HIV-1 Tat-induced downregulation of ocln. 52 Modification of the cav-1-ocln-Alix complex by overexpression of ocln also resulted in a prominent decrease in p24 levels in HIV-1-infected pericyte cultures ( Figure 6). These findings are consistent with our reports 25 in which we characterized ocln as a novel NADH oxidase that inhibits HIV-1 transcription by controlling SIRT-1 expression and activation in human brain pericytes.…”
mentioning
confidence: 96%
“…Morphological changes of pancreatic cancer cells were assessed by light microscopy. The sequences were as follows: miR-24 mimics, sense 5 '-UGG CUC AGU UCA GCA GGA ACA G-3', antisense 5'-GUU CCU GCU GAA CUG AGC CAU U-3'; mimics NC, sense 5'-UUC UCC GAA CGU GUC ACG UTT-3' , antisense 5'-ACG UGA CAC GUU CGG AGA ATT-3'; miR-24 inhibitor, 5'-CUG UUC CUG CUG AAC UGA GCC A-3'; inhibitor NC, 5'-CAG UAC UUU UGU GUA GUA CAA-3'. For in vivo studies, AsPC-1 cells were transduced with lentivirus (LV)-CASC2 (LV5-EF1a-GFP/Puro vector; Shanghai GenePharma Co., Ltd.) and LV-miR-24 (LV3-pGLV-h1-GFP-puro vector; Shanghai GenePharma Co., Ltd.), or LV-NC vectors (LV-CASC2-NC and LV-miR-24 NC; Shanghai GenePharma Co., Ltd.) as previously described (22). Briefly, AsPC-1 cells (5x10 5 per well) were plated in 6-well plates for 24 h; the medium was then replaced with fresh medium containing 8 µg/ml polybrene.…”
Section: Methodsmentioning
confidence: 99%
“…The cells (2 × 10 5 per well in 6-well plates) were transfected with LipoFiter™ Liposomal Transfection Reagent (Hanbio Biotechnology, China), as per the protocol provided by the lentivirus manufacturer. Retroviral infection was performed as previously described [26].…”
Section: Lentivirus Production and Infectionmentioning
confidence: 99%